EX SITU CONSERVATION PRIORITIES FOR THE PERUVIAN WILD TOMATO SPECIES (Solanum L. SECT. Lycopersicum (MILL.) WETTST.) - Vilchez, Dioliza (2019)
Tomato (Solanum lycopersicum) is a crop of global importance that has center of origin in Peru, with 11 species of wild relatives (CWR) occurring in the country. These CWR contain genetic material that could be used to improve currently cultivated species, and that is usually stored ex situ in germplasm banks. Hence, assessing the representativeness of germplasm banks is important to strengthen genetic improvement of tomatoes as well as their resilience to globally changing conditions. Here, we used gap analysis methodology on the 11 species of tomato CWR occurring in Peru. This methodology consists in seven steps that consider representativeness in terms of herbaria/germplasm banks, geography and environments within the country, in order to establish conservation priorities. We also assessed conservation priorities for the Instituto Nacional de Innovación Agraria (INIA), which is the main ex situ conservation Institution in Peru. Nationally, we found one species with high priority for conservation: Solanum huaylasense, and for INIA we found six species with high conservation priority: S. huaylasense, S. neorickii, S. chmielewskii, S. corneliomulleri, S. arcanum and S. chilense. We also found that the gap analysis methodology allowed for a proper prioritization of species and be readily applied to other species. We conclude by recommending strategies to improve the genetic coverage of the tomato germplasm held at INIA, as well as by discussing priorities for in situ conservation of tomato CWRs.